Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = (a - b ) - ( a - b - c) - ( 2b +c - a )
= a - b - a + b + c - 2b - c + a
= ( a - a + a) - (b - b + 2b) + ( c- c)
= a - 2b + 0
= a - 2b
A= (a - b) - (a - b - c) - (2b + c - a)
= a - b - a + b + c - 2b -c + a
= a - 2b
( a - b ) - ( a - b - c ) - ( 2b + c - a )
= a - b - a - b - c - 2b + c - a
= a - a - a - b - b - 2b - c + c
= a - 2b
A=a(2b-c)-b(a+c)-(c+b)
=2ab-ac-ab-bc-c-b
=(2ab-ab)-ac-bc-c-d
=ab-ac-bc-c-b
B=(a+3b)(c-d)-(3a-d)(b+c)-2c(b-a)+2b(a+d)
=a.(c-d)+3b.(c-d)-3a.(b+c)+d.(b+c)-2bc+2ac+2ab+2bd
=ac-ad+3bc-3bd-3ab-3ac+bd+cd-2bc+2ac+2ab+2bd
=(-3ab+2ab)+(3bc-2bc)+(ac-3ac+2ac)-ad+(-3bd+bd+2bd)+cd
=-ab+bc-ad+cd
a) A=(-a-b+c)-(-a-b-c)
A=-a-b+c+a+b+c
A=2c
b) Thay a=1;b=-1;c=-2 vào biểu thức A ,ta được:
A=(-1+1-2)-(-1+1+2)
A=(0+2)-(0+2)
A=2-2
A=2
A = (-a - b + c) - (-a - b - c)
= -a - b + c + a + b + c
= (a - a) + (b - b) + (c + c)
= 0 + 0 + 2c
= 2c
A = (-a - b + c ) - ( -a - b - c )
A = -a -b - c + a + b + c
A = (-a + a ) + (-b + b ) + (c + c)
A= 0 + 0 + 2c
A= 2c
Vay A= 2c
tik nha
Ta có A=(-a-b+c)-(-a-b-c)
=-a-b+c+a+b+c
=(-a+a)+(-b+b)+(-c+c)
=0
Khi a=1 ; b=-1;c=2
Thì A =(-1+1+2)-(-1+1-2)
=2-2
=0
(a+b)-(a-b)+(a+c)-(a+c)
=a+b-a+b+a-c-a-c
=a\(\times\)2-a\(\times\)2+b\(\times\)2-c\(\times\)2
(a+b-c)+(a-b+c)-(b+c-a)-(a-b-c)
=a+b-c+a-b+c-b-c+a-a+b+c
=a.3-a.1+b.2-b.2-c.2+c.2